Preterm uterine contractions ultimately delivered at term: safe but not out of danger. (April 2016) - Ganer Herman, Hadas; Miremberg, Hadas; Dekalo, Ann; Barda, Giulia; Bar, Jacob; Kovo, Michal
Abstract: Objectives: Patients with pregnancies complicated with premature uterine contractions (PMC), but delivered at term are considered as false preterm labor (PTL), and represent a common obstetric complication. We aimed to assess obstetric and neonatal outcomes of pregnancies complicated with PMC, but delivered at term, as compared to term normal pregnancies. Study design: Obstetric, maternal and neonatal outcomes of singleton pregnancies complicated with PMC between 24–33 6 /7 weeks (PMC group), necessitating hospitalization and treatment with tocolytics and/or steroids, during 2009–2014, were reviewed. The study group included only cases who eventually delivered ≥37 weeks, which were compared to a control group of subsequent term singleton deliveries who had not experienced PMC during pregnancy. Neonatal adverse composite outcome included: phototherapy, RDS, sepsis, blood transfusion, cerebral injury, NICU admission. Results: The PMC group ( n  = 497) was characterized by higher rates of nulliparity ( p  = 0.002), infertility treatments ( p  = 0.02), and polyhydramnios ( p  < 0.001), as compared to controls ( n  = 497). Labor was characterized by higher rates of instrumental deliveries ( p  = 0.03), non-reassuring fetal heart rate tracings ( p  < 0.001) prolonged third stage of labor ( p  = 0.04), and increased rate of post-partum maternal anemia (Hb < 8 g/dL) p  = 0.004, in the PMC group as compared to controls. Neonates in the PMC groups had lower birth weights compared to controls, 3149 g ± 429 vs. 3318 g ± 1.1, p  < 0.001, respectively. By logistic regression analysis, PMC during pregnancy was independently associated with neonatal birth-weight <3rd percentile (adjusted OR 4.6, 95% CI 1.5–13.7). Conclusions: Pregnancies complicated with PMC, even-though delivered at term, entail adverse obstetric and neonatal outcomes, and may warrant continued high risk follow up.